2015
DOI: 10.5740/jaoacint.12-461
|View full text |Cite
|
Sign up to set email alerts
|

A Method Detection Limit for Bacillus anthracis Spores in Water Using an Automated Waterborne Pathogen Concentrator

Abstract: The method detection limit (MDL, 99% chance of detecting a positive result in a single replicate), as per the United States Code of Federal Regulations, was determined for a protocol using an ultrafiltration based automated waterborne pathogen concentration device. Bacillus anthracis Sterne strain spores were seeded at low levels into 100 L reagent water samples. Suspect colonies were confirmed through morphological, chemical, and genetic tests. Samples of 100 L (n=14) of reagent water were seeded with five B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The detection limit identified in this study agrees with previous work on other organisms, which has demonstrated that viable spores of Bacillus artrophaeus at levels of <10 CFU l −1 can be concentrated and recovered from >100 l tap water (Kearns et al, ) and that high recovery rates (>95%) can be obtained for Escherichia coli and human polyomavirus using DEUF (Li et al, ). Also, Humrighouse et al () determined the method detection limit for a tangential flow ultrafiltration‐based automated waterborne pathogen concentrator using the same filter type as in this study. Their experimental data showed a method detection limit for Bacillus anthracis of approximately 6 CFU 100 −l with the confidence interval 4·8–8·4 CFU 100 −l .…”
Section: Discussionmentioning
confidence: 95%
“…The detection limit identified in this study agrees with previous work on other organisms, which has demonstrated that viable spores of Bacillus artrophaeus at levels of <10 CFU l −1 can be concentrated and recovered from >100 l tap water (Kearns et al, ) and that high recovery rates (>95%) can be obtained for Escherichia coli and human polyomavirus using DEUF (Li et al, ). Also, Humrighouse et al () determined the method detection limit for a tangential flow ultrafiltration‐based automated waterborne pathogen concentrator using the same filter type as in this study. Their experimental data showed a method detection limit for Bacillus anthracis of approximately 6 CFU 100 −l with the confidence interval 4·8–8·4 CFU 100 −l .…”
Section: Discussionmentioning
confidence: 95%
“…Spore Preparation-The strain of B. globigii spores used in this study was originally obtained from J. Wright, U.S. Army, Dugway Proving Grounds, UT. Spores were prepared following the procedure outlined by Humrighouse et al, (2015). Briefly, spores were prepared in a generic sporulation media and purified using gradient separation with RenoCal-76 (Bracco Diagnostics, Princeton, NJ).…”
Section: Microorganismsmentioning
confidence: 99%
“…The CDC developed a protocol for use in laboratories for the concentration of large volume drinking water samples (Polaczyk et al, 2008;Hill et al, 2005). In addition, the US EPA in conjunction with Idaho National Laboratory (INL) developed the Water Sample Concentrator (WSC), a semi-automated portable device for concentrating large volume samples in the field (Carpenter et al, 2016, Humrighouse et al, 2015. While differing in certain details, the two tangential flow HFUF methods yielded comparable recovery of the organisms studied, which included viruses, vegetative bacteria, bacterial endospores and protozoa (EPA and CDC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Sensor performance is often measured by receiver operating characteristic curves (Hubaux and Vos, 1970), or through a method detection limit (CFR 2017) although this may be less commonly used for evaluating biological detection techniques (Humrighouse et al 2015). Sensors may also be described in terms of their sensitivity, specificity, quantitative accuracy, minimum detection limit, precision and accuracy.…”
mentioning
confidence: 99%